Utilizing social media marketing in a traditional MSME: An insider action research - Disu, Kristel Joy A. (Animo Repository, 2022)
Many view the adoption of social media in businesses' marketing as the new way of doing business, allowing firms to create more intimate relationships with stakeholders (Brodie et al., 2007). Although there is a growing concern that businesses “must” engage with social media or risk losing out on new opportunities (Drury, 2008), the literary sources are limited in showing guidance on how highly traditional MSMEs, particularly in the Philippines, can overcome distinct challenges and utilize the benefits of social media to manage fundamental stakeholder relations, especially those with the customers. As such, this study aims to create a firm understanding of the operational aspects around social media’s functionality, the resource levels required to manage it effectively, and the strategic perspective needed to harness the benefits in a meaningful way; thus, seeks to answer the issue of “How can traditional MSMEs transition to a social media-forward marketing strategy to increase their market presence?” I concluded by presenting an integrated framework that seeks to understand the social media marketing adoption of MSMEs, by referencing related research and the learnings from the two cycles of action research enacted in this study. The proposed framework highlights the importance of uncovering the barriers restricting and factors reinforcing social media adoption, together with understanding the target customers in the platform, which then forms part of the strategic intent and direction of the company, and thereafter influences the four aspects of social media marketing management of the company (i.e., messaging/projecting, monitoring, assessing, and responding), with the presumption that it will be able to positively create an impact on the business.